From innovation to exporting or vice versa? Causal link between innovation activity and exporting in Slovenian microdata - Jože P. Damijan; Črt Kostevc; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
firm productivity and export decision are closely related to its innovation ac- tivity. Product innovation may play a more important role in the decision to start exporting, while the decision for process innovation may be triggered by success- ful exporting. This suggests that the causality between innovation and exporting may run from product innovation to exporting and conesequently from exporting to process innovation and reverse productivity improvements. Using detailed mi- crodata, including innovation survey, industrial production survey and infirmation on trade, for Slovenian firms in 1996-2002 we investigate this dual causal relation- ship between firms' innovation and exporting activity. We find no evidence for the hypothesis that either product or process innovations increase the probability of becoming a first time exporter, but find consistent support both in the innovation survey as well as in the industrial production survey that exporting does lead to pro- ductivity improvements. These, however, are likely to be related to process rather than product innovations and are limited to a sample of medium and large sized first time exporters only.
Keywords: D24; F14; F21; 330; Firm heterogeneity; innovation; exporting; productivity; matching; Innovation; Produktivität; Internationaler Wettbewerb; Fertigungssteuerung; Slowenien